WEBRESOURCE FOR SELFREGULATED FOREIGN LANGUAGE ACQUISITION: CONTENT AND LEARNING POSSIBILITIES - Anna K. Kuptsova (Moscow Polytechnic University, 2016)
Abstract. One of the most important directions of improving modern methods and ways of foreign language acquisition is introducing interactive methods into the educational process. Based on the literature review of Russian and international materials the author defines the importance of self-regulated learning and computer-assisted language learning. The author provides a list of multimedia resources as didactic tools and examines web-resources for autonomous learning. The analysis of learning possibilities of foreign Web-resources for learning academic English is provided. The researcher studies sections and types of exercises, which importance is assessed by the data received from surveying NRU HSE students. The survey results allow to make conclusions about how the usage of web-resources is urgent in the higher education and to give recommendations how to create a web-resource.